Antiviral Activity, Safety, and Pharmacokinetics of Bictegravir as 10-Day Monotherapy in HIV-1-Infected Adults - Gallant, Joel E; Thompson, Melanie; DeJesus, Edwin; Voskuhl, Gene W; Wei, Xuelian; Zhang, Heather; White, Kirsten; Cheng, Andrew; Quirk, Erin; Martin, Hal (Journal of acquired immune deficiency syndromes (1999), 2017)
To evaluate antiviral activity, safety, and pharmacokinetics of short-term monotherapy with bictegravir (BIC), a novel, potent HIV integrase strand transfer inhibitor (INSTI). Phase 1b, randomized, double-blinded, adaptive, sequential cohort, placebo-controlled study. HIV-infected adults not taking antiretroviral therapy were randomized to receive BIC (5, 25, 50, or 100 mg) or placebo once daily for 10 days. Primary endpoint was time-weighted average change from baseline to day 11 (DAVG11) for plasma HIV-1 RNA. HIV-1 RNA, adverse events (AEs), and laboratory assessments were evaluated through day 17. Twenty participants were enrolled (n = 4/group). Mean DAVG11 ranged from -0.92 to -1.61 across BIC doses versus -0.01 for placebo. Significant reductions in plasma HIV-1 RNA from baseline at day 11 were observed for all BIC doses compared with placebo (P < 0.001); mean decreases were 1.45-2.43 log10 copies/mL. Increased BIC exposures correlated with increased reduction in plasma HIV-1 RNA from baseline on day 11. Three participants on BIC (50 or 100 mg) achieved plasma HIV-1 RNA <50 copies/mL by end of study. Median Tmax ranged from 1.0 to 1.8 hours (day 1, postdose) and 1.3-2.7 hours (day 10), with median t1/2 ranging from 15.9 to 20.9 hours. No participant developed primary INSTI-R substitution through day 17. BIC was well tolerated, with no discontinuations because of adverse events. BIC is a novel, potent, unboosted INSTI that demonstrated rapid, dose-dependent declines in HIV-1 RNA after 10 days of monotherapy. BIC was well tolerated, and displayed rapid absorption and a half-life supportive of once-daily therapy in HIV-infected subjects.